2015
DOI: 10.1051/matecconf/20153502004
|View full text |Cite
|
Sign up to set email alerts
|

Contact and Non-contact Measurements of Grinding Pins

Abstract: Abstract. The paper presents the results of contact and non-contact measurements of external profiles of selected grinding pins. The measurements were conducted in order to choose the appropriate measuring technique in the case of the considered measurement task. In the case of contact measurements the coordinate measuring machine ACCURA II was applied. The used coordinate measuring machine was equipped with the contact scanning probe VAST XT and the Calypso inspection software. Contact coordinate measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Through the movement of the X-direction translation stage and Z-direction vertical stage, the grinding wheel profile was moved into the FOV. Autofocus [13] of the grinding wheel profile was realized by moving the CCD camera along the optical axis (Y axis) and searching for the maximally sharp position in the image sequence. Then, through X direction and Z direction translation, different section images of the grinding wheel profile could be obtained.…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the movement of the X-direction translation stage and Z-direction vertical stage, the grinding wheel profile was moved into the FOV. Autofocus [13] of the grinding wheel profile was realized by moving the CCD camera along the optical axis (Y axis) and searching for the maximally sharp position in the image sequence. Then, through X direction and Z direction translation, different section images of the grinding wheel profile could be obtained.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Magdziak et al [13] employed a coordinate measuring machine to measure the profile of a grinding wheel and concluded that the contact method presented a lack of repeatability, which is associated with the different measurement parameters applied during coordinate measurements.…”
Section: Introductionmentioning
confidence: 99%